Evaluación De Las Dimensiones Curriculares Para Determinar El Nivel De Alcance De Los Perfiles Profesionales De Los Egresados De La Carrera De Educación Básica De La Universidad Técnica De Babahoyo, Extensión Quevedo - Brahan Peralta Dolores Del Carmen (2015)
"Evaluation of the Curricular dimensions to determine the level of scope of the professional profiles of the graduates of the School of Basic Education of the Technical University of Babahoyo, Extension Quevedo", was aimed to evaluate the curricular dimensions to determine the level of scope occupational profiles of the graduates of the race in question. An assessment of the preferred theme oriented to academia and students was conducted dimension. The source of information were teachers and students. In the analysis group of teachers there was only one Master, ICTs are considered as reference for curriculum planning, the ideas of students are considered by 17 percent, six questions were answered by two elements of the sample and make connection with the axes curricular learning and curriculum planning block; and that the evaluation of learning there is weakness in the attitudinal element. To be given easier for teachers to train constantly, attending seminars inside and outside the country in order to have better teaching learning.